A novel mutation in GATA6 causes pancreatic agenesis. Issue 1 (17th January 2014) - Stanescu, Diana E.; Hughes, Nkecha; Patel, Puja; De León, Diva D.
<x xml:space="preserve">Abstract</x> Heterozygous mutations in GATA6 have been linked to pancreatic agenesis and cardiac malformations. The aim of this study was to describe a new mutation in GATA6 in an infant with pancreatic agenesis, associated with truncus arteriosus and absent gallbladder. Clinical data were obtained from chart review. Gene sequencing was performed on genomic DNA. The patient was a female infant diagnosed shortly after birth with a severe cardiac malformation, absent gallbladder, anomalous hepatic blood flow, unilateral hydronephrosis and hydroureter, neonatal diabetes, and pancreatic exocrine insufficiency. Despite prolonged intensive management care, she died at 3 months of age because of cardiac complications. Analysis of her genomic DNA revealed a novel missense mutation of GATA6. The novel mutation described in this case extends the list of GATA6 mutations causing pancreatic agenesis and cardiac malformations.